The Influence Of Social Capital And Human Capital On The Performance Of Small And Medium Enterprises In The City Of North Padang Lawas - Replita; Nursyirwan Effendi; Taufika Ophiyandri; Alfan Miko (Sharia Journal and Education Center Publishing, 2025)
The food and beverage industry in North Padang Lawas requires a lot of labor. Companies use labor as social and human capital. The purpose of this study is to descriptively analyze, analyze the effect of human capital and social capital on the performance of food and beverage SMEs in North Padang Lawas City, and then make recommendations to improve SME performance. The methods used in this study include performance value analysis (IPA), fish bar diagrams, and structural formula analysis (SEM) with a Partial Least Squares (PLS) approach. The results of SEM analysis showed that. As a result, it is recommended to improve the performance of SMEs through supporting activities, such as establishing a quality control system and production implementation standards, improving the facilities owned by SMEs, and participating in training that improves the ability of SME employees.